2016
DOI: 10.1002/cncr.30071
|View full text |Cite
|
Sign up to set email alerts
|

Association of androgen metabolism gene polymorphisms with prostate cancer risk and androgen concentrations: Results from the Prostate Cancer Prevention Trial

Abstract: Background Prostate cancer is highly influenced by androgens and genes. We investigated whether genetic polymorphisms along the androgen biosynthesis and metabolism pathways are associated with androgen concentrations or risk of prostate cancer or high-grade disease from finasteride treatment. Methods A nested case-control study from the Prostate Cancer Prevention Trial using cases drawn from men with biopsy-proven prostate cancer and biopsy-negative, frequency-matched controls was conducted to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Genetic variations in the pathways in which the chemoprevention agents act may influence the efficacy of the agent. Finasteride acts by inhibiting the enzyme 5α reductase which is mediated by genes of the SRF5A family [31]. Polymorphisms in the SRFA genes have been reported which affect the efficacy of Finasteride [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in the pathways in which the chemoprevention agents act may influence the efficacy of the agent. Finasteride acts by inhibiting the enzyme 5α reductase which is mediated by genes of the SRF5A family [31]. Polymorphisms in the SRFA genes have been reported which affect the efficacy of Finasteride [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies on polymorphisms in SRD5A1 and SRD5A2 have suggested its association with PCa risk and PCa recurrence [25][26][27]. However, SRD5A2 rs9282858, the common nonsynonymous single nucleotide polymorphism was found not significantly associate with PCa risk [25]. Therefore, further studies are warranted to identify how the epigenetic change of these enzymes effects on PCa.…”
Section: Srd5a2 Promoter Methylation Was Negatively Associated With Smentioning
confidence: 99%
“…Interestingly, the GG genotype for SNP rs472402 was associated with increased risk of high-grade cancer (OR ¼ 1.7; 95% CI, 1.05-2.75; ref. 19) but not with low-grade cancer, and we found that this GG genotype is also associated with a 55% reduction of high-grade cancer risk by finasteride. This SNP has recently been shown to be associated with d-amphetamine response in a genome-wide association study (22).…”
Section: Discussionmentioning
confidence: 45%
“…As the set of SNPs we analyzed were picked from candidate genes related to prostate cancer, some of the identified effect-modifying SNPs have been reported to be associated with risk of prostate cancer in previous PCPT analyses. Five of the six effect-modifying SNPs we detected in SRD5A1 (rs3736316, rs3822430, rs472402, rs1560149, and rs248797) were also significantly associated with risk of high-grade cancer in the placebo arm (19). Interestingly, the GG genotype for SNP rs472402 was associated with increased risk of high-grade cancer (OR ¼ 1.7; 95% CI, 1.05-2.75; ref.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation